A Systematic Review of Studies on Digital Migration and Coverage of Digital Television Services - Isabirye, Joel; Muhereza, Bobrich Mwecumi (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This review systematically examines studies published on the relationship between digital migration and coverage of digital television broadcasting services. It was guided by four objectives: to examine the cost of digital migration and coverage of digital broadcasting services; to analyze consumer awareness and coverage of digital broadcasting services; to examine subscription payments and coverage of digital broadcasting services; and to analyze special interactive services and coverage of digital television broadcasting services. The inclusion criteria were based on studies that linked to the objectives of the review. Effort was also made to sieve and select studies that were scholarly in nature. The review employed a longitudinal descriptive design covering studies published between 2010 and 2018. 35 studies were purposively sampled and classified into periodization (date of publication), geographical scope, content scope, and methodological orientation. It was found that most of the studies were published close to 2015 which was the International Telecommunications Union (ITU) deadline for member countries to migrate to digital television broadcasting. The studies were limited in geographical scope focusing on only 9 out of the 193 member countries of the ITU. Costs, customer awareness, subscription payments, and special interactive services were found to have a strong effect on coverage of digital television broadcasting services.